2016
DOI: 10.1590/0102-311x00085915
|View full text |Cite
|
Sign up to set email alerts
|

Home or community-based pulmonary rehabilitation for individuals with chronic obstructive pulmonary disease: a systematic review and meta-analysis

Abstract: Home or community-based pulmonary rehabilitation for individuals with chronic obstructive pulmonary disease: a systematic review and meta-analysis Reabilitação pulmonar domiciliar ou comunitária para indivíduos com doença pulmonar obstrutiva crônica: revisão sistemática e meta-análise Rehabilitación pulmonar domiciliaria o comunitaria para individuos con enfermedad pulmonar obstructiva crónica: revisión sistemática y metaanálisis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 61 publications
(140 reference statements)
2
56
0
1
Order By: Relevance
“…Importantly, however, the findings triangulate well those of similar recent work in this area by Neves et al . In their review of 23 studies of 1258 participants, the authors compared community or home‐based PR to no PR ( n = 19 studies) or hospital‐based PR ( n = 4 studies).…”
supporting
confidence: 79%
“…Importantly, however, the findings triangulate well those of similar recent work in this area by Neves et al . In their review of 23 studies of 1258 participants, the authors compared community or home‐based PR to no PR ( n = 19 studies) or hospital‐based PR ( n = 4 studies).…”
supporting
confidence: 79%
“…Positive outcomes valued by all stakeholders, such as 'improving exercise tolerance' and 'reducing and taking control over dyspnoea' are well-recognized benefits of pulmonary rehabilitation, and studies usually use the same outcome measures. [30][31][32] Therefore, these outcomes are likely to integrate a future core outcome set for pulmonary rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Although 'improving functional performance', 'managing fatigue, improving stamina and exercise recover', 'staying motivated and feeling confident', 'having meaningful support' and 'having a purpose, feeling of self-efficacy', were valued outcomes among all stakeholders, their assessment in pulmonary rehabilitation is not standardized and is rarely reported in the literature. [30][31][32] Functionality is fundamental, as it translates to patients' quotidian and influences informal carers' burden. 33 Fatigue is one of the major symptoms limiting patients; therefore, its common/routine assessment for adequate management is important.…”
Section: Discussionmentioning
confidence: 99%
“…Again, this large ( n = 287) non‐inferiority RCT showed promising results. Furthermore, two systematic reviews have recently demonstrated a lack of difference in key outcomes between home‐ and centre‐based PR models …”
Section: Pulmonary Rehabilitation In Copdmentioning
confidence: 99%